Thermal Comfort Status In A Naturally Ventilated Tropical Livestock Building: Combined Effect Of Orientation And Amount Of Opening On Rabbit Production - Ogunjimi, L.A.O.; Ogunwande, G.A.; Osunade, J.A. (Ife Journal of Technology, 2010)
The effect of orientation and amount of opening (vent) using two buildings orientations and two opening levels in a rabbit house under a naturally ventilated condition was studied in this research. Sixteen (16) rabbits of same age bracket were used, distributed randomly into four (4) partitioned pens each. The rabbits were fed with commercial pellet feed and given water ad libitum for 91 days. The two orientations and openings (inlet) were 90o and 45o to the direction of the prevailing North-south wind and 50% and 30% of 1.44 m2 area, respectively, and also a control building having 100% opening but oriented in east-west direction. Temperature and relative humidity of the buildings were observed twice daily through a period of thirteen weeks. Feed intake, weight gain (WG), feed efficiency (FE), pulse rate (PR), rectal temperature (RT) and respiration rate (RR) of the rabbits were equally taken for each week of the experiment. From the results of the experiment it was observed that building orientation and amount of opening greatly affect the internal comfort level of animal buildings. The 50% opening/900 orientation building provides the least Temperature-Humidity Index (THI = 32.49 0C) and hence the highest thermal comfort situation for the rabbits corresponding to the highest WG and FE of 76.88 gm and 0.68; lowest RT and RR of 38.85 oC and 41.08 rpm, respectively. Hence it was observed that rabbits’ performances characteristics of WG and feed utilization efficiency of the rabbit are significantly correlated with the comfort levels of the pen; the correlation coefficient, R2, ranges between 0.92 and 0.98.